The effects of the 1-min preceptor and problem-based clinical educations on nursing students' critical thinking - Azade Safa; Mohsen Adib-Hajbaghery; Tayebeh Moradi (Kashan University of Medical Sciences, 2021)
Background: There are inconsistencies about the best clinical teaching method for strengthening nursing students' critical thinking (CT). Objective: This study is aimed to compare the effects of the one-min preceptor (OMP) and problem-based learning (PBL) clinical education on nursing students' CT. Methods: This was a randomized controlled trial. All forty 3rd-year nursing students who had taken the Medical-Surgical Nursing III clinical course were recruited to the study through the census method in 2016 in Kashan University of Medical Sciences, Kashan, Iran. The students were randomly allocated into three groups of 13 to pass their clinical course via the OMP, the PBL, or the conventional clinical education methods, respectively. In the first session and at the end of the last session, the students completed the California CT Skills Test Form B. The one-way analysis of variance and the Kruskal-Wallis and Mann-Whitney tests were used to analyze the data. Results: Students' mean age was 21.77 ± 1.32 years. There were no significant differences in baseline CT score among the conventional (11.17 ± 1.64), OMP (10.58 ± 1.34), and PBL (10.79 ± 1.18) groups (P = 0.894). However, at the end of the study, the difference among the groups regarding CT score was significant (12.17 ± 1.89, 13.69 ± 1.10, and 13.64 ± 1.44; P = 0.049). Conclusion: OMP and PBL can be potentially effective in improving students' CT ability. Therefore, these methods can be used in clinical nursing education to improve students' CT ability.